Risk Management of Occupational Health and Safety on Mechanical, Formwork, and Reinforcing Iron Work Process at X Building Project 2020 - Fadhila, Rusiana Ayutri (Universitas Pembangunan Nasional Veteran Jakarta, 2020)
Risk management is a work process included recognizing, identifying, and assessing risk hazards. This program is one of the components that illustrates the fundamental of occupational health and safety in a company. The purpose was to identify the category of each risks and find the most accurate way to control. This research is semi-quantitative with descriptive design, using interview guidelines, observation checklist, and self-assessing risk based on AS/NZS 4360:2004. Result showed highest risks for mechanical work are risk of workers could had an electric shock while repairing electrical tools; formwork are risk of workers can fall while doing a job on column (over 2 meters) and risk of workers can inhale wood dust while working on wood’s fabrication; lastly, reinforcing iron work are risk of workers can be breathing on particles of irons or concrete dust while doing an iron fabrication. Corona virus was also highest risk for workers. Therefore, researcher gave recommendation by: (1) Installation of barrier around electrical panels area plus cable hanger; (2) Using cross brace scaffolding for activities on the edge of building; (3) Application of dry exhaust system for dusts on formwork area; (4) Using an on-tool extraction for manual grinder on iron fabrications area.Key Words: Building Project, Construction, Risk Management